Issues and Options for Improving Engagement between the World Bank and Civil Society Organizations - World Bank (Washington, DC, 2016)
The purpose of this paper is to assess the World Bank's recent relations with civil society organizations (CSOs), that is, nongovernmental organizations and not-for-profit organizations, and to propose options for promoting more effective civic engagement in Bank-supported activities and managing associated risks in the future. The analysis in this paper points to four main issues and challenges for the Bank as it seeks to achieve more constructive and effective engagement with CSOs in the future: 1) Promoting best practices for civic engagement; 2) Closing the gap between expectations, policy and practice; 3) Adapting to changes in global and national civil society; and 4) Achieving greater Bank-wide coherence and accountability. To attain these objectives, the report proposes ten priority actions: Establishing new global mechanisms for Bank-CSO engagement to help promote mutual understanding and cooperation; establish a Bank-wide advisory service/focal point for consultations and feedback; piloting a new Bank-wide monitoring and evaluation system for civic engagement; Conduct a review of Bank funds available for civil society engagement in operations and policy dialogue, and explore possible realignment or restructuring. reviewing the Bank's procurement framework; instituting an integrated learning program for Bank staff and member governments as well as capacity-building for CSOs on how to work effectively with the Bank and its member governments; holding regular meetings of senior management and periodically with the Board to review Bank/civil society relations; developing and issuing new guidelines for Bank staff on the institution's approach, best practices, and a framework for engagement with CSOs; emphasizing the importance of civil society engagement in preparing Country Assistance Strategies (CAS) as well as in CAS monitoring and evaluation; and developing tools for analytical mapping of civil society.